Analisa Perhitungan Struktur Atas Bangunan Gedung Perkantoran Di Wilayah Kota Pekalongan - Tisnawati Tisnawati; Dwi Kumalasari (Pena Jurnal Ilmu Pengetahuan dan Teknologi, 2023)
Infrastructure development in Indonesia experiences rapid development every year, including in Pekalongan City. Infrastructure development in Pekalongan City starts from the construction of roads, buildings, public facilities, and so on. The Pekalongan City Government has made an alternative that is in accordance with the above conditions, namely by constructing offices to improve or meet the needs of public facilities and realize sustainable infrastructure progress. The construction of existing high-rise buildings must be properly planned in accordance with applicable regulations. Based on SNI 2847-2013, regarding calculation procedures for buildings, it is explained that the loads that must be calculated for planning a structure are dead loads, live loads, wind loads, earthquake loads, and combinations of these loads. The building under review is a two-storey office building with reinforced concrete construction. The analysis is carried out with the help of the SAP computer program. Before analyzing, first make a working drawing design with the help of the Autocad program. The final results in this study are in the form of dimensions of structural elements that are planned to be strong and resistant to loads and economical in terms of cost. While the analysis of the main structure in the form of plates, beams, and columns.